Die Here is soos 'n krygsman en hy skree soos 'n vrou in barendsnood (Jes. 42:13,14) - WS Prinsloo (Acta Theologica)
Most exegetes are of the opinion that, on the grounds of formgeschichtliche criteria, Isaiah 42:13 and 14 are not directly related to one another. However, in this article it is indicated that the two similes have purposely been placed together and should be read as closely related. The function of both similes in Isaiah 42:13 and 14 is to focus the attention on the active intervention of Yahweh during the exilic period. This applies particularly to the simile in verse 14 which should therefore not be seen as a symbol of need or suffering or as an indication of the femininity of Yahweh.